Theoretical Progress on the Relationship between the Structures and Properties of Perovskite Solar Cells. Issue 9 (26th June 2020) - Geng, Wei; Tong, Chuan‐Jia; Zhang, Yanning; Liu, Li‐Min
Abstract: Organic–inorganic lead halide perovskite solar cells have attracted great attention due to their high conversion efficiency, easy preparation, and low cost. In spite of impressive development, some fundamental scientific issues regarding perovskites have not been resolved, such as the inclusion of toxic Pb, their poor stability under moisture, oxygen, heat, and/or light conditions, and their hysteretic current–voltage behavior. In the past few years, theoretical approaches have been extensively and successfully applied to the investigation of perovskite solar cells. Here, the current theoretical progress in perovskite photovoltaic applications is summarized from a theoretical perspective, including important theoretical results in fundamental structures and properties, computational design of perovskites by high throughput calculation and machine learning, hysteresis‐related ion migration, compositional substitution and mixing, surface reconstruction, mechanisms of degradation and passivation, interface carrier recombination, and the distribution and rotation of organic cations caused polarization and domain. Abstract : Current theoretical progress in perovskite photovoltaic applications, including the important theoretical results of fundamental structures and properties from density functional theory (DFT), machine learning, molecular dynamics, DFT, and Monte Carlo, is summarized. Additionally, the effect of distribution and rotation of organic cations is emphasized.